Synthesis and Characterization of Trivalent Cerium Complexes of p-tert-Butylcalix[4,6,8]Arenes: Effect of Organic Solvents - Md. Hasan Zahir (Journal of Chemistry)
Reaction of Ce3+ with p-tert-butylcalix[n]arene (n=4,6,8) yields purple crystalline complexes structurally as [Ce(p-tert-butylcalix[4]arene-3H)2(NO3)(DMF)x](2 − x)DMF (1), [Ce(p-tert-butylcalix[6]arene-4H)2(NO3)(DMF)x](3 − x)DMF (2), and [Ce(p-tert-butylcalix[8]arene-7H)2(NO3)(DMF)6] (3), where DMF=N,N-dimethylformamide. The properties and coordination characteristics of the three calixarene complexes were determined by elemental analyses, electronic absorption, X-ray absorption spectroscopy (EXAFS), TG-DTA, FT-IR, SEM, and 1H-NMR spectroscopy. The effect of various organic solvents on complexes 1, 2, and 3 has been discussed based on results from electronic absorption spectra. The polar protic solvents showed the most significant molar extinction coefficients in comparison with those of nonpolar and polar aprotic solvents. The Ce3+ ions in the complexes are proved to combine with the ligand phenolic groups, oxygen atoms of DMF molecules, and/or OH− ions.